The Investigation of Polycyclic Aromatic Hydrocarbon and Oil Degrading Bacteria Isolated from The Marina Port Ancol, Jakarta Bay - Puspita Lisdiyanti; Yopi Yopi; Tutik Murniasih (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2011)
Polycyclic Aromatic Hydrocarbons (PAHs) as well as crude oil are widespread environmental pollutants. The contamination of air, soil, freshwater (surface water and groundwater), and marine environments by PAHs as well as crude oil has been reported. Of concern to public health is the fact that many PAHs or their metabolites are mutagenic, carcinogenic, or both. North Java coastal area such as Jakarta Bay is the polluted marine area in Indonesia as a result from anthropogenic wastes and the oil spill. Although evaporation and photo-oxidation play an important role in oil detoxification, ultimate and complete degradation is accomplished mainly by marine micro flora, and being dominant in this function. Certain bacteria are well-known could consume and degrade the PAHs as well as crude oil. Therefore investigating the potential PAH and oil degrading marine bacteria is important. In this study, we collected sample from oil polluted area in Marina Port Ancol, Jakarta Bay and isolated four PAH substrates and Arabian crude oil degrading marine bacteria using enrichment method and direct isolation method. As result, 223 strains could degrade PAHs, among these strains, 94 strains could degrade phenanthrene, 23 strains degrade fluoranthene, 92 strains could degrade dibenzotiophen, 14 strains could degrade phenotiazin and 106 isolates degrade crude oil.Key words: polycyclic aromatic hydrocarbons, crude oil, degrading bacteria, bioremediation.